Investigation of some biochemical parameters, hematological changes, neopterin and procalcitonin levels in dogs with Canine distemper virus - Batı, YU; Kırmızıgül, AH (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was conducted to determine serum neopterin and procalcitonin levels in dogs with distemper. The animal material of the study consisted of 35 patients diagnosed with distemper and 15 healthy dogs of different breeds and genders between the ages of 1.5-6 months. Blood cell counts like white blood cells (WBC), lymphocytes (LYM), granulocytes (Gra), red blood cells (RBC), hematocrit (HCT), thrombocytes (THR), gra%, and hemoglobin (Hb) showed a statistically significant difference (P<0.001).Similarly, when the monocyte values of the sick animals were compared with the monocyte values of the animals in the control group, the difference (P<0.01) was seen to be significant. The biochemical parameters urea, alkaline phosphatase (ALP), and amylase (AMY) levels of sick animals were compared to those of healthy animals. There was a statistically significant difference (P < 0.001) between the two groups.Again, serum GGT and glucose levels of sick animals showed significant differences compared to the same values of healthy animals (P<0.01). While the serum neopterin concentration of the sick animals was 4.94 ± 0.31 nmol/L, the value of the dogs in the control group was determined as 3.02 ± 0.33 nmol/L. When these two values were compared statistically, the difference (P<0.001) was determined to be significant. Similarly, the serum procalcitonin concentration of the sick animals was determined as 65.11 ± 3.12 ng/L, while the serum procalcitonin level of the dogs in the control group was found to be 44.05 ± 3.20 ng/L. When serum procalcitonin values in both groups were compared statistically, the difference (p<0.001) was determined to be significant. As a result, since distemper disease is a multisystemic disease, changes in serum biochemical and hematological parameters were observed separately. In addition, serum neopterin and procalcitonin changes in dogs with distemper were determined to be significantly higher than in the control group (P<0.001). With these results, it was concluded that serum neopterin and procalcitonin biomarkers may play an important diagnostic role in distemper disease, and these parameters were determined for the first time in distemper disease.